Global gene expression patterns in Porites white patch syndrome: Disentangling symbiont loss from the thermal stress response in reef‐building coral. Issue 20 (15th September 2020) - Kenkel, Carly D.; Mocellin, Veronique J. L.; Bay, Line K.
Abstract: The mechanisms resulting in the breakdown of the coral symbiosis once the process of bleaching has been initiated remain unclear. Distinguishing the process of symbiont loss from the thermal stress response may shed light on the cellular and molecular pathways involved in each process. This study examined physiological changes and global gene expression patterns associated with white patch syndrome (WPS) in Porites lobata, which manifests in localized bleaching independent of thermal stress. In addition, a meta‐analysis of global gene expression studies in other corals and anemones was used to contrast differential regulation as a result of disease and thermal stress from patterns correlated with symbiotic state. Symbiont density, chlorophyll a content, holobiont productivity, instant calcification rate, and total host protein content were uniformly reduced in WPS relative to healthy tissue. While expression patterns associated with WPS were secondary to fixed effects of source colony, specific functional enrichments combined with a lack of immune regulation suggest that the viral infection putatively giving rise to this condition affects symbiont rather than host cells. Expression in response to WPS also clustered independently of patterns in white syndrome impacted A. hyacinthus, further supporting a distinct aetiology of this syndrome. Expression patterns in WPS‐affected tissues were significantly correlated with prior studies that examined short‐term thermal stress responses independent of symbiotic state, suggesting that the majority of expression changes reflect a nonspecific stress response. Across studies, the magnitude and direction of expression change among particular functional enrichments suggests unique responses to stressor duration and highlights distinct responses to bleaching in an anemone model.